2017
DOI: 10.1007/s00209-017-1937-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher order approximation of analytic sets by topologically equivalent algebraic sets

Abstract: It is known that every germ of an analytic set is homeomorphic to the germ of an algebraic set. In this paper we show that the homeomorphism can be chosen in such a way that the analytic and algebraic germs are tangent with any prescribed order of tangency. Moreover, the space of arcs contained in the algebraic germ approximates the space of arcs contained in the analytic one, in the sense that they are identical up to a prescribed truncation order.2010 Mathematics Subject Classification. 32S05, 32S15, 13B40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A stronger version of Theorem 3.7 was given in [5] where it was shown that such a homeomorphism h can be found with any prescribed order of tangency at the origin. Question 3.8.…”
Section: Application: Analytic Set Germs Are Homeomorphic To Algebrai...mentioning
confidence: 99%
“…A stronger version of Theorem 3.7 was given in [5] where it was shown that such a homeomorphism h can be found with any prescribed order of tangency at the origin. Question 3.8.…”
Section: Application: Analytic Set Germs Are Homeomorphic To Algebrai...mentioning
confidence: 99%